2007
DOI: 10.1186/1477-7525-5-66
|View full text |Cite
|
Sign up to set email alerts
|

Validity and reliability of the Spanish version of the DN4 (Douleur Neuropathique 4 questions) questionnaire for differential diagnosis of pain syndromes associated to a neuropathic or somatic component

Abstract: Background: This study assesses the validity and reliability of the Spanish version of DN4 questionnaire as a tool for differential diagnosis of pain syndromes associated to a neuropathic (NP) or somatic component (non-neuropathic pain, NNP).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
165
5
13

Year Published

2010
2010
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(198 citation statements)
references
References 24 publications
15
165
5
13
Order By: Relevance
“…It is also suggested that the exclusion of a neutral point will draw the respondent to make a decision one way or the other. The more recent scientific studies have used this type of scale demonstrating that by eliminating a neutral level provides a better measure of the intensity of participants' attitudes or opinions' (see for example Perez et al, 2007) …”
Section: Methodsmentioning
confidence: 99%
“…It is also suggested that the exclusion of a neutral point will draw the respondent to make a decision one way or the other. The more recent scientific studies have used this type of scale demonstrating that by eliminating a neutral level provides a better measure of the intensity of participants' attitudes or opinions' (see for example Perez et al, 2007) …”
Section: Methodsmentioning
confidence: 99%
“…The SF-McGill questionnaire 14 identified severe scores for the descriptors of 'hot-burning' , 'aching' , 'tender' , 'tiring-exhausting' , 'fearful' , 'punishing-cruel' during the previous week, while pain adjectives such as 'sharp' , 'gnawing' , 'heavy' , 'sickening' were also present and rated as moderate. Application of the Spanish version of the DN4 questionnaire 15 indicated the presence of below-level NP (7/10), which was described as 'burning' , 'cold pain' , 'tingling' , 'pins and needles' with 'numbness' , and which was accompanied by hypoaesthesia to touch and pinprick (left L5 AIS sensory testing point). Interestingly, the DN4 questionnaire failed to detect NP at the level of SCI based on descriptors, although touch hypoaesthesia was detected for this pain subtype.…”
Section: Resultsmentioning
confidence: 99%
“…Ainsi, une mauvaise utilisation des outils peut conduire à biaiser les résultats d'enquêtes épidémiologiques en population générale [7]. Enfin, il a été montré que la sensibilité et la spécificité des outils de dépistage étaient moindres en cas de douleur faible (< 4/10) [36]. [9].…”
Section: Limites Des Outils De Dépistageunclassified